Platelet hyperreactivity explains the bleeding abnormality and macrothrombocytopenia in a murine model of sitosterolemia - Kanaji, Taisuke (American Society of Hematology, 2013)
Sitosterolemia is a rare, autosomal recessive disease caused by mutations in the adenosine triphosphate-binding cassette transporter genes ABCG5 or ABCG8 that result in accumulation of xenosterols in the body. Clinical manifestations include tendon xanthomas, premature coronary artery disease, hemolytic anemia, macrothrombocytopenia, and bleeding. Although the effect of sterol accumulation on the predisposition for atherosclerosis is evident, how xenosterol accumulation leads to defects in platelet physiology is unknown. Sitosterolemia induced in Abcg5- and Abcg8-deficient mice fed a high plant sterol diet resulted in accumulation of free sterols in platelet plasma membranes, leading to hyperactivatable platelets characterized by constitutive binding of fibrinogen to its αIIbβ3 integrin receptor, internalization of the αIIbβ3 complex, generation of platelet-derived microparticles, and changes in the quantity and subcellular localization of filamin. The latter was associated with macrothrombocytopenia, shedding of GPIbα, impaired platelet adhesion to von Willebrand factor, and inability to form stable thrombi. Plasma levels of soluble GPIbα were strongly correlated with plasma sitosterol levels in samples from human sitosterolemic patients, implicating a similar mechanism of sterol-induced platelet passivation in the human disease. Intercalation of plant sterols into the plasma membrane therefore results in dysregulation of multiple platelet activation pathways, leading to macrothrombocytopenia and bleeding.